The star cluster survivability after gas expulsion is independent of the impact of the Galactic tidal field - Shukirgaliyev, Bekdaulet; Parmentier, Geneviève; Berczik, Peter; Just, Andreas (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We study the impact of the tidal field on the survivability of star clusters following instantaneous gas expulsion. Our model clusters are formed wit
Gesehen am 31.05.2019